A non-orthogonal joint coordinate system for the calculation of anatomically practical joint torque power in three-dimensional hip joint motion - Sado, N.; Yoshioka, S.; Fukashiro, S. (International Journal of Sport & Health Science, 2017)
We examine the advantages of a non-orthogonal joint coordinate system (JCS) in calculating each anatomical torque's power through comparison with a segment coordinate system (SCS) of the distal segment. To clarify the differences between coordinate systems, kinematic data were collected from 12 male participants swinging their legs laterally and anteriorly under two conditions: the toe facing forward and facing laterally. The mechanical power and work exerted by each hip anatomical torque in JCS and SCS were calculated. With the toe facing forward, there is no significant difference between the two methods. The largest energy generators were abduction torque for lateral swing and flexion torque for anterior swing. With the toe facing laterally, in JCS, these results were consistent for both lateral swing (abduction: 0.21 ± 0.06 J/kg; flexion: 0.06 ± 0.04 J/kg) and anterior swing (flexion: 0.35 ± 0.09 J/kg; adduction: 0.01 ± 0.01 J/kg). However, in SCS, the largest energy generator for lateral swing changed from abduction (0.08 ± 0.07 J/kg) to flexion torque (0.22 ± 0.12 J/kg). For anterior swing, the hip adduction torque generated as large energy (0.14 ± 0.08 J/kg) as hip flexion torque (0.20 ± 0.08 J/kg) in SCS. Therefore, although SCS resulted in an inconsistency between power generator and movement due to hip external rotation, JCS avoided it, regardless of leg position, allowing JCS to investigate the power generation/absorption of each anatomical torque, particularly during long axial rotation.